Between Science and Ethics in Rebecca Harding Davis's "Waiting for the Verdict" - Šesnić, Jelena (Array, 2008)
Rebecca Harding Davis’ s still relatively obscure novel, _Waiting for the Verdict_ (serialised in 1867), is a complex study of the vicissitudes of race and class during the Civil War and in its immediate aftermath. Using an array of sentimental/reformist, proto-realist and realist narrative and stylistic procedures, the author creates an ideologically dense text which is ultimately unable to break away from the incipient contradictions, whether on the level of its narrative execution or on the level of its very heterogeneous content. This fascinating, if at times contradictory, heterogeneity is illustrated in the argument, principally through focus on the issues of colour and those of class or social status. These issues are cast within the prevailing forms of racialist discourses and theories of society, unfolding under the heading of scientific Darwinism and environmentalism on the one hand, and its counterpart, religious, sentimental, and reformist discourses on the other.